The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/molecules22101690
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Absolute Configuration, and Antiproliferative Activity of Abietane and Icetexane Diterpenoids from Salvia ballotiflora

Abstract: From the aerial parts of Salvia ballotiflora, eleven diterpenoids were isolated; among them, four icetexanes and one abietane (1–5) are reported for the first time. Their structures were established by spectroscopic means, mainly 1H- and 13C-NMR, including 1D and 2D homo- and hetero-nuclear experiments. Most of the isolated diterpenoids were tested for their antiproliferative, anti-inflammatory, and radical scavenging activities using the sulforhodamine B assay on six cancer cell lines, the TPA-induced ear ede… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 51 publications
3
37
0
1
Order By: Relevance
“…Their structures were established by spectroscopic means, mainly 1 H- and 13 C-NMR, while the AC of 110 , 111 , and 112 (Figure 28) was determined by X-ray diffraction analysis and VCD. 65…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their structures were established by spectroscopic means, mainly 1 H- and 13 C-NMR, while the AC of 110 , 111 , and 112 (Figure 28) was determined by X-ray diffraction analysis and VCD. 65…”
Section: Resultsmentioning
confidence: 99%
“…Their structures were established by spectroscopic means, mainly 1 H-and 13 C-NMR, while the AC of 110, 111, and 112 (Figure 28) was determined by X-ray diffraction analysis and VCD. 65 The aerial parts of Salvia clinopodioides gave abietanes 113, 115, and 117, together with icetexane 118 (Figure 29). The AC of 113 and 115 was verified by VCD of their acetates 114 and 116.…”
Section: Terpenoidsmentioning
confidence: 99%
“…Abietane diterpenes (ADs), extracted from a variety of plant sources, display a wide variety of biological activities, including antibacterial, antioxidant, anti-inflammatory, and antifungal activities, amongst others (Çadirci et al, 2012;Wu et al, 2012;Hanson, 2013;Gonzalez, 2015). In particular, the antiproliferative activity of both phenolic-type (carnosic acid and ferruginol) and quinone-type (aethiopinone, salvipisone, and 1oxoaethiopinone) ADs has been reported in different cancer cell lines (Gonzalez, 2015;Akaberi et al, 2015;Esquivel et al, 2017). Aethiopinone and salvipisone from S. sclarea induce caspase-3 mediated apoptosis in a time-and concentration-dependent manner in leukemia cells (Rozalski et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…We found that the yield of DAM, ICT, and DEOX was lower than 0.005% [ 6 ], and as a result, only few experiments with these compounds were performed [ 9 ]. Therefore, the in vivo models, quantitation of IL-1β and IL-10 in LPS-stimulated macrophages, anti-arthritic activity, membrane stabilization assay, the apoptosis and the antitumor assay were assessed only with ECL standardized with DEOX as the phytochemical marker.…”
Section: Discussionmentioning
confidence: 99%
“…From this plant species, two diterpene quinones have been isolated, icetexone (ICT) and conacytone [7] as well as other diterpenes, such as 19-deoxyicetexone (DEOX), 19-deoxyisocetexone (DIC), and 7,20-dihydroanastomosine (DAM), among others [8]. Other isolated compounds from Salvia ballotiflora include 7α-acetoxy-6,7-dihydroicetexone, and anastomosine, these two compounds have shown cytotoxic activity against the cancer cell lines U251 and SKLU-1, and an anti-inflammatory effect on acute ear edema induced by TPA in mice [9]. Additional, some studies have found that different diterpenes exhibited an important anti-inflammatory effect [10].…”
Section: Introductionmentioning
confidence: 99%